Emotional availability: foster caregiving experiences - Nelson, Dean R., author; Waite, Alina M., advisor; Makela, Carole J., committee member; Timpson, William M., committee member; Biringen, Zeynep, committee member (Colorado State University. Libraries, 2012)
The purpose of the study was to investigate if the emotional availability of caregivers is explanatory for successful adolescent foster care placement--from initial placement of an adolescent to age eighteen or emancipation from foster care, as mandated by the state of Colorado. Emotional availability of foster caregivers and the phenomenon's impact are critical when anticipating placement of an adolescent in a foster caregiving environment. An adolescent anticipates, desires, and needs a safe and enduring foster placement. The emotional impact affects the adolescent as well as the caregiver from the initial introduction to the foster home to emancipation from the foster care system. When an adolescent is placed in a foster home, two areas must be addressed by the caregiver. First, the adolescent arrives without any history with the foster family. Secondly the adolescent does not know the expectations of the foster caregivers, and the reciprocal is true for the caregivers. Initially, a foster adolescent needs a safe environment and the foster caregiver desires an adolescent who will express those desires. These two areas are difficult in the beginning of a foster placement and require positive parenting skills by the foster caregiver to facilitate each and nurture a quality relationship between the adolescent and the foster caregiver. Participants in the study included 6 adults who previously fostered adolescents within their homes. Four of the participants were adult females and two of the participants were adult males. All participants were from northeast Colorado and when formally fostering adolescents were licensed foster caregivers by the state of Colorado. The participants engaged in an extensive journaling exercise which answered 22 questions in a narrative format, which corresponded to the structure of the Emotional Availability (EA) Scales®, developed by Biringen and colleagues (Biringen, Robinson, & Emde, 2008). These areas are the components of emotional availability--sensitivity, structuring, nonintrusiveness, nonhostility, and child responsiveness/child involvement. Based on a constructivist paradigm the study focused on the experience within the caregiver-adolescent dyad as described by the caregiver's lived experience, both as an adult and a youth. There are always many interpretations and no foundational process by which ultimate truth can be determined. However, the trustworthy criteria of credibility, transferability, and dependability are the hallmarks of the paradigm and of this study. The research methodology was based on an inductive analysis and interpretation of the journal entries, which lead to an intent to develop a reality and thus, explain the caregiver-adolescent phenomenon and how emotional availability is an essential tenet of foster caregiving. The study found that if caregivers described engagement with their own caregivers while being raised, then they would be more fully engaged with their foster adolescent during placement. The research question, "does emotional availability inform the foster caregiving Experience," was supported in this study in the participants' responses. Emotional availability does inform foster caregiving. Therefore, the recommendation for this research is to evaluate perspective foster caregivers of adolescents as to their capacity to use the tenets of emotional availability.
Keywords: emotional; caregiving; foster; adolescent; availability